2015
DOI: 10.1590/0100-2945-052/14
|View full text |Cite
|
Sign up to set email alerts
|

Adubação Nitrogenada E Potássica Em Goiabeiras ‘Paluma’:ii. Efeito No Estado Nutricional Das Plantas

Abstract: RESUmo -a adequada adubação mineral de pomares de goiabeira, sob manejo intensivo, é fator preponderante na produtividade, e o acompanhamento do estado nutricional das plantas contribui para a eficiência desta prática agronômica. Objetivou-se pesquisar o efeito de diferentes doses de nitrogênio e potássio sobre o estado nutricional de goiabeiras 'Paluma'. o experimento foi conduzido em Vista alegre do alto-SP, em pomar irrigado, com sete anos de idade, manejado com podas de frutificação, durante quatro ciclos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 7 publications
(8 reference statements)
2
7
0
4
Order By: Relevance
“…These results are comparable in variability to the report by Amorim et al (2015), who worked with mineral nutrition in guava (Psidium guajava L.) plants, where Ca concentrations in leaves increased with increasing N doses.…”
Section: Macronutrient Contentssupporting
confidence: 88%
See 1 more Smart Citation
“…These results are comparable in variability to the report by Amorim et al (2015), who worked with mineral nutrition in guava (Psidium guajava L.) plants, where Ca concentrations in leaves increased with increasing N doses.…”
Section: Macronutrient Contentssupporting
confidence: 88%
“…Therefore, accordingly to Amorim et al (2015), the leaf contents are not directly related to nutrient concentrations in soil, but rather implies an effect of the interaction with nitrogen fertilization. This may be related to the higher nitrogen uptake in relation to P, Mg and S or due to the dilution effect caused by a faster growth of fertilized camu-camu plants with higher N doses.…”
Section: Macronutrient Contentsmentioning
confidence: 99%
“…There were five trees per plot and the three central trees were monitored. Leaf nutrient concentration, soil fertility and fruit production were determined during three consecutive cycles (Amorim et al, 2015). Balances were designed to improve the understanding of N and K fertilizer effects on the soil using the sequential binary partition in Table 1 used to compute ilr coordinates.…”
Section: Compositional Analysis and Cnd Application: Examplesmentioning
confidence: 99%
“…Nitrogen (N) is the nutrient required in largest amount by most plants and the second most required by the guava crop in its initial development stage (FRANCO et al, 2007). A number of studies have been carried out with crops such as banana (MAIA et al, 2003), carambola (LEAL et al, 2007), guava (AMORIM et al, 2015) and castor bean (LIMA et al, 2015), and have shown beneficial effects of nitrogen application on plant growth and development. However, studies related to nitrogen application under salt stress conditions are scarce in guava, especially in the production phase.…”
Section: Introductionmentioning
confidence: 99%